2016
DOI: 10.3389/fmats.2016.00002
|View full text |Cite
|
Sign up to set email alerts
|

3D RVE Models Able to Capture and Quantify the Dispersion, Agglomeration, and Orientation State of CNT in CNT/PP Nanocomposites

Abstract: The focus of this study is to investigate the capabilities of three dimensional (3D) RVE models in predicting the tensile modulus of carbon nanotube/polypropylene (CNT/PP) composites, which differ slightly in the dispersion, agglomeration, and orientation states of CNT within the PP matrix. The composites are made using melt mixing followed by either injection molding or melt spinning of fibers. The dispersion, agglomeration, and orientation of CNT within the PP are experimentally altered by using a surfactant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 64 publications
(77 reference statements)
1
12
0
Order By: Relevance
“…Considering several cases by varying the parameters, they concluded the CNT alignment to be a more influencing parameter than the CNT waviness while predicting elastic properties of random CNT composites. It is further supported by results obtained by Bhuyian et al [14,27] who also incorporated less-studied parameters such as a soft CNT/polymer interphase and CNT agglomeration. Fiber/matrix interface has been discussed to be of importance by Reifsnider et al [1].…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…Considering several cases by varying the parameters, they concluded the CNT alignment to be a more influencing parameter than the CNT waviness while predicting elastic properties of random CNT composites. It is further supported by results obtained by Bhuyian et al [14,27] who also incorporated less-studied parameters such as a soft CNT/polymer interphase and CNT agglomeration. Fiber/matrix interface has been discussed to be of importance by Reifsnider et al [1].…”
Section: Introductionsupporting
confidence: 71%
“…The theoretical, experimental and multiscale modelling aspects of CNT based polymer composites are reviewed extensively by [6][7][8][9][10][11]. Depending upon the CNT orientation, there can be random [12][13][14][15][16] as well as aligned [17][18][19][20] CNT composites. Previous studies found that the properties of these composites are greatly influenced by the morphological parameters such as CNT orientation, dispersion, waviness, diameter, inter-CNT spacing, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the polymer of PLLA was melted uniformly and the melt flow rate of PLLA achieves stability [ 46 , 47 ]. However, the melt of PLLA polymer would be cooled agglomeration as it flow to the end of the 840 μm spinneret due to its temperature of the 840 μm spinneret lower glass conversion temperature of PLLA polymer [ 48 ]. We can observe that the diameter of fibre became tiny with receiving distance increased when 840 μm spinneret was used.…”
Section: Resultsmentioning
confidence: 99%
“…Unit cell model applies a representative volume element (RVE) composed of phases with different thermal conductivities, and the thermal conductivity of RVE is calculated according to the thermal resistance network method [17] . This model is also widely used in numerical simulation [18,19] . Zehner et al [20] calculated the thermal conductivity of the point-contacted spherical particle reinforced composites by constructing a cylindrical unit cell.…”
mentioning
confidence: 99%